Development of Body Movement Skills Using Illustrative Music as a Stimulus in Dance Learning - Venny Rosalina; Susmiarti Susmiarti; Robby Ferdian (Gondang: Jurnal Seni dan Budaya, 2023)
This research explores the use of illustrative music as a stimulus for skill development in the field of body movement within the Dance Education program at Padang State University (UNP). Illustrative music aids in motivation, rhythm regulation, concentration, emotional expression, memory, creativity, body mobility, and flexibility in the dance body movement courses. The research employs a qualitative methodology involving interviews, observations, and document analysis to investigate the impact of illustrative music. The findings of the study indicate that the use of illustrative music, such as Minangkabau ethnic music and classical music, during dance body movement exercises provides a positive boost to skill development, emotional expression, and movement comprehension within the art of dance. Through this approach, the Dance Education program at UNP creates a deep, holistic learning environment for body movement in the art of dance.